2022
DOI: 10.1002/ep.13865
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to the synthesis of CuFe2O4@CeO2 direct Z‐scheme with a core‐shell structure for enhanced photo‐degradation of methyl violet under ultraviolet and visible‐light irradiation

Abstract: A direct Z-scheme photocatalyst CuFe 2 O 4 @CeO 2 core-shell was applied in the photocatalytic degradation of the methyl violet dye 2B (MV). In first, CuFe 2 O 4 and CeO 2 were synthesized via sol-gel method, and then CuFe 2 O 4 @CeO 2 nanocomposite was prepared using microwave process. The nanoparticles were characterized by thermogravimetric analysis (TG and derivative thermogravimetry [DTG]), atomic absorption spectroscopy (AAS), Brunauer-Emmett-Teller (BET) analysis, Xray diffraction (XRD), Fourier transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Hence, his adsorption onto the surface of semiconductor was scarcely. In the case of methyl orange (Abbas & Trarib 2021) and Methyl Violet (Touahra et al 2022), using TiO 2 as semiconductor, higher decolorization efficiency was reported under acidic conditions. In the case of ZnO, decolorization was reached an initial maximum at pH 4, then decreases around the neutral region and picks up again to reach a maximum at pH 11.…”
Section: Effect Of Initial Ph On the Photocatalysis Of Cby 3g-pmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, his adsorption onto the surface of semiconductor was scarcely. In the case of methyl orange (Abbas & Trarib 2021) and Methyl Violet (Touahra et al 2022), using TiO 2 as semiconductor, higher decolorization efficiency was reported under acidic conditions. In the case of ZnO, decolorization was reached an initial maximum at pH 4, then decreases around the neutral region and picks up again to reach a maximum at pH 11.…”
Section: Effect Of Initial Ph On the Photocatalysis Of Cby 3g-pmentioning
confidence: 99%
“…TiO 2 and ZnO have been widely used as photocatalysts due to their high activity, desirable physical and chemical properties, low cost, high specific surface area and availability (Ghribi et al 2020;Aoudjit et al 2021;Shathy et al 2022). The mechanism that has been suggested regarding the heterogeneous photocatalytic degradation of dyes can be expressed by the fact that when a catalyst is exposed to UV radiation, electrons are promoted from the valence band to the conduction band, as a consequence, an electron-hole pair is produced (Touahra et al 2022).…”
Section: Introductionmentioning
confidence: 99%